Fetal Tissues Are Exposed to Biologically Relevant Free Thyroxine Concentrations during Early Phases of Development - Rosa Calvo; Eric Jauniaux; Béatrice Gulbis; M. Asunción; Christine Gervy; Bernard Contempré; Gabriella Morreale de Escobar (2002)
Maternal hypothyroxinemia in early pregnancy is often associated with irreversible effects on neuropsychomotor development. To evaluate fetal tissue exposure to maternal thyroid hormones up to midgestation, we measured total T4 and free T4 (FT4), T3, rT3, TSH, and possible binding proteins in first trimester coelomic and amniotic fluids and in amniotic fluid and fetal serum up to 17 wk. Samples were obtained before interruption of maternal-fetal connections. The concentrations in fetal compartments of T4 and T3 are more than 100-fold lower than those in maternal serum, and their biological relevance for fetal development might be questioned. We found, however, that in all fetal fluids the concentrations of T4 available to developing tissues, namely FT4, reach values that are at least one third of those biologically active in their euthyroid mothers. FT4 levels in fetal fluids are determined by both their T4-binding protein composition and the T4 or FT4 in maternal serum. The binding capacity is determined ontogenically, is independent of maternal thyroid status, and is far in excess of the T4 in fetal fluids. Thus, the availability of FT4 for embryonic and fetal tissues would decrease in hypothyroxinemic women, even if they were euthyroid. A decrease in the availability of FT4, a major precursor of intracellular nuclear receptor-bound T3, may result in adverse effects on the timely sequence of developmental events in the human fetus. These findings ought to influence our present approach to maternal hypothyroxinemia in early pregnancy regardless of whether TSH is increased or whether overt or subclinical hypothyroidism is detected.